NF-κB in the crosshairs: Rethinking an old riddle - Bennett, Jason (Int J Biochem Cell Biol, 2018)
Constitutive NF-κB signalling has been implicated in the pathogenesis of most human malignancies and virtually all non-malignant pathologies. Accordingly, the NF-κB pathway has been aggressively pursued as an attractive therapeutic target for drug discovery. However, the severe on-target toxicities associated with systemic NF-κB inhibition have thus far precluded the development of a clinically useful, NF-κB-targeting medicine as a way to treat patients with either oncological or non-oncological diseases. This minireview discusses some of the more promising approaches currently being developed to circumvent the preclusive safety liabilities of global NF-κB blockade by selectively targeting pathogenic NF-κB signalling in cancer, while preserving the multiple physiological functions of NF-κB in host defence responses and tissue homeostasis.